Evidence-Based interventions of Norovirus outbreaks in China - Tianmu Chen; Haogao Gu; Ross Ka-Kit Leung; Ruchun Liu; Qiuping Chen; Ying Wu; Yaman Li (BMC, 2016)
Abstract Background In resource-limited settings where laboratory capacity is limited and response strategy is non-specific, delayed or inappropriate intervention against outbreaks of Norovirus (NoV) are common. Here we report interventions of two norovirus outbreaks, which highlight the importance of evidence-based modeling and assessment to identify infection sources and formulate effective response strategies. Methods Spatiotemporal scanning, mathematical and random walk modeling predicted the modes of transmission in the two incidents, which were supported by laboratory results and intervention outcomes. Results Simulation results indicated that contaminated water was 14 to 500 fold more infectious than infected individuals. Asymptomatic individuals were not effective transmitters. School closure for up to a week still could not contain the outbreak unless the duration was extended to 10 or more days. The total attack rates (TARs) for waterborne NoV outbreaks reported in China (n = 3, median = 4.37) were significantly (p < 0.05) lower than worldwide (n = 14, median = 41.34). The low TARs are likely due to the high number of the affected population. Conclusions We found that school closure alone could not contain Norovirus outbreaks. Overlooked personal hygiene may serve as a hotbed for infectious disease transmission. Our results reveal that evidence-based investigations can facilitate timely interventions of Norovirus transmission.